ANALISIS KELAYAKAN INVESTASI USAHA BUDIDAYA IKAN AIR TAWAR DI KABUPATEN SUMBA TIMUR - Indra Hadi Hamdan; Alliny Hutar (Fakultas Ekonomi Universitas IBA, 2023)
This study aims to analyze the feasibility of investing in freshwater fish farming in Kambera District, East Sumba Regency, East Nusa Tenggara Province. This is done by researchers based on a phenomenon that shows that freshwater fish farming has great potential, but there are still some things that are still considered lacking, especially in business management. This study took a sample of 6 businesses in the Kamera District area using a saturated sampling technique. This research also uses three formulas to analyze the feasibility of business investment, namely: payback period (PP), net present value (NPV), and net benefit-cost ratio (Net B/C). The results show that, based on the results of the study, it can be said that investment in freshwater fish farming is declared feasible for 4 businesses, while 2 businesses is not feasible. The business feasibility assessment using the net benefit-cost ratio (Net B/C) method was declared feasible because 6 businesses were able to generate income from each cost incurred. Meanwhile, the investment feasibility is declared unfeasible by using the net present value (NPV) method, because the operating income has not been able to return the investment.